THE ROLE OF INFRASTRUCTURE IN ENSURING REGIONAL ECONOMIC DEVELOPMENT (Scientific journal of the Fergana State University, 2025)
Infrastructure plays a pivotal role in fostering regional economic development by enhancing connectivity, productivity, and inclusivity. This study examines the impact of transport, energy, and digital infrastructure on reducing regional disparities and enabling sustainable growth. Findings reveal that rural regions often face infrastructure deficits, hindering their economic potential. Recommendations include prioritizing equitable investments, promoting digital infrastructure, adopting eco-friendly practices, and strengthening governance frameworks. These strategies aim to achieve balanced regional development and long-term economic resilience through sustainable and inclusive infrastructure initiatives.